Glucose, urea, and creatinine laboratory tests in people starting antiretroviral therapy with dolutegravir or efavirenz: a cohort study in Belo Horizonte, Brazil (Research, Society and Development, 2022)
Goal: In this study, we aimed to monitor the blood glucose, urea, and creatinine laboratory tests in treatment-naive individuals, initiating ART with an antiretroviral regimen containing EFV or DTG, searching for a contribution to the understanding of the safety of these drugs in use in the real world, followed up for 72 weeks. Methods: Cohort study with a follow-up of people living with HIV initiating antiretroviral therapy. Results: An increase in blood creatinine levels at 24 and 48 weeks and blood glucose levels at 48 weeks (p=0.017) was observed in the group using Dolutegravir. Those using Efavirenz evidenced an increase in creatinine levels at 48 weeks (p=0.007), blood glucose levels at 72 weeks (p=0.009), and urea levels at 48 weeks (p=0.023). Being male (p=0.044) and having more than 13 schooling years (0.044) explained the change in creatinine levels. Tobacco use (p=0.006), illicit drug use (p=0.009), and schooling greater than or equal to 13 study years (p=0.038) were independently associated with changes in urea levels. The therapeutic regimen with Efavirenz (OR=8.20; 95% CI=1.32-51.05; p=0.024) and schooling greater than or equal to 13 study years were independently associated with increased blood glucose concentration. Conclusions: The DTG regimen was associated with increased serum creatinine levels for up to 42 weeks and was transient and returning to the levels observed before the start of ART. The Efavirenz regimen was related to increased serum glucose levels, and the Dolutegravir therapy was the preferred regimen.